Da vinculação dos tribunais administrativos tributários à sistemática de precedentes do Código de Processo Civil: uma análise fundamentada no princípio constitucional da eficiência - Pinto, Edson Antônio Sousa Pontes (2018)
The system of precedents established by the Civil Procedure Code bases on the need for integrity and stability of the legal system, as well as on the imperative guarantee of the uniqueness of the decisions set by the courts that have the competence to standardize the jurisprudence. The objective is to ensure that equal cases are treated in the same way, thus fulfilling the fundamental right of equality laid down in the Federal Constitution. That is, to apply precedents is to exercise the jurisdictional activity guided on the coherence of judgments, based on the arguments already established by the high courts, but above all is to bring rationality to the legal system and to the courts avoiding that these decisions be discarded, ignored or disrespected without any plausible reasoning, or reasons for it. Therefore, all those who have the power to judge, even if in an administrative jurisdiction, should adhere to and respect precedents established by the major courts, since they are bound to them by the constitutional principle of efficiency. This principle mandates that the Public Administration achieve the same purpose with the use of fewer resources, that is, applying this principle in judicial activity, the administrative judge must adhere to established precedents, considered public goods, avoiding that a thesis already judged and pacified is ignored or discarded without its due overruling. The present paper aims to demonstrate that the Tax Administrative Courts must follow precedents, because they are bound by Civil Procedure Code, but, above all, by a duty of efficiency, ordered by such principle, which dictates public agents and obliges them to act with rationality in administrative functions and activities, including here the judicial exercise of such courts